Use of Cytological examination in the diagnosis of dog and cat diseases (Research, Society and Development, 2021)
This work verified the use of cytological diagnosis, as a method of identification of disorders in dogs and cats domiciled in the municipality of Barra-BA seen at the University Veterinary Hospital (HVU) of the Federal University of Western Bahia (UFOB). The study was conducted from the analysis of cytological samples related to clinical cases seen in the years 2018 and 2019. A total of 711 animals were seen, of these counted 105 (101 canines and 4 felines - 59 females and 46 males) requests for the cytological examination. Most of the animals (28.57%) were 6 to 10 years old, with the prevalence of No Defined Breed animals (62.38%). The inflammatory processes were diagnosed in 43.80% of the cases, identified as having infectious cause in 86.90% (30% by Leishmania spp., 27.5% bacterial infections, 27.5% by the yeast Malassezia spp. and other 15% by association of this fungus with bacteria). Inflammatory processes of non-infectious origin were recorded in 13.10% cases (84% infiltrated by inflammatory cells and 16% as lick dermatitis). Non-inflammatory processes were observed in 19.05% of the samples, 95% of which were of neoplastic origin, (63.15% TVT, 21.05% Squamous Cell Carcinoma, 10.05% Adenocarcinoma and 5.30% Trichoblastoma). Among the non-inflammatory and non-neoplastic processes (5%) an epidermal cyst was diagnosed (100%). The applicability of cytological diagnosis in dogs and cats denotes importance since it helps veterinarians in confirming clinical suspicions, allowing the issuance of diagnostic reports, establishment of treatments and epidemiological data that enable the implementation of control measures of diseases.